Distribution of heavy metal (Pb, Cd and Hg) concentrations in sediment of Bone River, Gorontalo - Miftahul Khair Kadim; Endang Herawati Yuli; Diana Arfiati; Asus Maizar Suryanto Hertika; Faizal Kasim (Depik, 2022)
The concentration of three heavy metals Pb, Cd and Hg ware measured in Bone River, Gorontalo sediment. The heavy metal pollution on sediment in Bone River have not been explored longitudinally. The samples were taken in July 2021 at 8 stations.  The trend of metals ware observed in sediment as PbCdHg. The level of studied metals Cd and Hg did not exceed the safe limit by ANZECC, OSQG LEL and CCME TEL meanwhile Pb was met the limit by by ANZECC. However, the investigated showed that fluctuations due to differences in the characteristics of each location. Contamination factor (CF) and geoaccumulation index (Igeo) demonstrated that the sediment samples were low contamination and lightly polluted. Contamination by heavy metals in the Bone River implies that the conditions are much frightening for the biota and residents around the river.